2021
DOI: 10.1007/s10461-021-03210-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Dissemination of a Web-Based Video Promotes PrEP Contemplation and Conversation Among US Women Engaged in Care at Planned Parenthood

Abstract: We evaluated the acceptability and impact of a web-based PrEP educational video among women ( n = 126) by comparing two Planned Parenthood centers: one assigned to a Web Video Condition and one to a Standard Condition. Most women reported the video helped them better understand what PrEP is (92%), how PrEP works (93%), and how to take PrEP (92%). One month post-intervention, more women in the Web Video Condition reported a high level of comfort discussing PrEP with a provider (82% vs. 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…One month after the intervention, women who were enrolled in the web-based counseling method were more likely to be comfortable discussing PrEP with a provider (82 vs. 48%) and were more likely to be thinking about PrEP (36 vs. 4%). However, no women in this study initiated PrEP at 1 year follow up [44]. In a study evaluating 515 encounters in a family planning clinic, 76% of which were for abortion care, authors found the screening rate of their implementation strategy to be 51.3%, with those who were African American or who presented for abortion care to be more likely to be Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Methodsmentioning
confidence: 78%
“…One month after the intervention, women who were enrolled in the web-based counseling method were more likely to be comfortable discussing PrEP with a provider (82 vs. 48%) and were more likely to be thinking about PrEP (36 vs. 4%). However, no women in this study initiated PrEP at 1 year follow up [44]. In a study evaluating 515 encounters in a family planning clinic, 76% of which were for abortion care, authors found the screening rate of their implementation strategy to be 51.3%, with those who were African American or who presented for abortion care to be more likely to be Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Methodsmentioning
confidence: 78%